High‐resolution spectral characterization of two photon states via classical measurements. Issue 5 (24th June 2014) - Eckstein, Andreas; Boucher, Guillaume; Lemaître, Aristide; Filloux, Pascal; Favero, Ivan; Leo, Giuseppe; Sipe, John E.; Liscidini, Marco; Ducci, Sara
<x xml:space="preserve">Abstract</x> A technique to characterize two‐photon quantum states from parametric fluorescence with unprecedented spectral resolution is demonstrated by performing a classical DFG experiment. This technique has the potential to speed up design and testing of massively parallel integrated nonlinear sources by providing fast and reliable quality control, and it allows for high‐fidelity spectral engineering of novel quantum light states. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>